Determinants of real exchange rates: An empirical investigation - Vikas Kakkar; Isabel Yan (Bank of Finland, Institute for Economies in Transition (BOFIT), 2014)
The large and persistent deviations of nominal exchange rates from their purchasing power parities comprise a key stylized fact in international economics. This paper sheds light on these persistent deviations by combining two disparate strands of empirical work. The first strand focuses on real economic shocks such as sectoral technology shocks suggested by the celebrated Balassa-Samuelson model, whereas the second strand emphasizes monetary shocks which create persistent effects on both the real interest rate and the real exchange rate. We also hypothesize a third factor which may affect real exchange rates - shocks to the global financial system, which we proxy by the real price of gold. Although each factor in isolation has limited explanatory power, we find that these three factors in conjunction can successfully explain the medium to long run movements in 14 bilateral U.S. dollar real exchange rates from 1970 to 2006. The three factors are sectoral total factor productivity differentials, real interest rate differentials, and the real price of gold, representing real shocks, monetary shocks, and shocks to the global financial system, respectively. We document evidence suggesting that bilateral U.S. dollar real ex-change rates are cointegrated with these three factors.
URN:NBN:fi:bof-201408071970
Keywords: F31; F41; 330; purchasing power parity; Balassa-Samuelson model; cointegration